2014
DOI: 10.1007/s10926-013-9492-3
|View full text |Cite
|
Sign up to set email alerts
|

How Work Impairments and Reduced Work Ability are Associated with Health Care Use in Workers with Musculoskeletal Disorders, Cardiovascular Disorders or Mental Disorders

Abstract: Purpose the aim of this study was to explore how work impairments and work ability are associated with health care use by workers with musculoskeletal disorders (MSD), cardiovascular disorders (CVD), or mental disorders (MD). Methods in this cross-sectional study, subjects with MSD (n = 2,074), CVD (n = 714), and MD (n = 443) were selected among health care workers in 12 Dutch organizations. Using an online questionnaire, data were collected on individual characteristics, health behaviors, work impairments, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Third, all data were self-reported; therefore, response bias cannot be excluded. Self-reported data, however, are widely used in occupational medicine and it has shown to be a good predictor for long-term sick leave and productivity loss (Reeuwijk et al 2014 ). Finally, the categories of common diseases were fairly broad and severity was not assessed; for example, both employees with a heart attack and employees with high blood pressure were combined in the CVD subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, all data were self-reported; therefore, response bias cannot be excluded. Self-reported data, however, are widely used in occupational medicine and it has shown to be a good predictor for long-term sick leave and productivity loss (Reeuwijk et al 2014 ). Finally, the categories of common diseases were fairly broad and severity was not assessed; for example, both employees with a heart attack and employees with high blood pressure were combined in the CVD subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…At the start, all invited employees were informed that the information was also used for scientific purposes and that filling in the questionnaire was interpreted as informed consent. All data were anonymized for privacy protection (Reeuwijk et al 2014 ). In total, 8426 of the 15,358 invited employees responded (55%).…”
Section: Methodsmentioning
confidence: 99%
“…Since a reduced work ability has proven to predict long-term sickness absence, decreased work performance, productivity loss, more healthcare use and early exit from work, it is important to assess the concept of work ability (Ahlstrom et al, 2010;Alavinia, Molenaar, & Burdorf, 2009;Reeuwijk, Robroek, Hakkaart, & Burdorf, 2014;Sell, 2009). A large Finnish health survey showed that in an average working population of 30-64 year olds, 8% of the women and 7% of the men reported having limited work ability (measured using WAI); for physically demanding work these percentages were 13% and 10%, respectively (Gould et al, 2008).…”
Section: Work Abilitymentioning
confidence: 99%
“…Work impairments and reduced work ability were associated with greater health care use among workers. 35 These findings suggest that addressing work-related problems in workers with common disorders may help reduce health care needs. Based in the results, age, household size, and possession of health insurance are associated with work ability among the study population.…”
Section: Discussionmentioning
confidence: 97%